Seismic Performance of Precast Concrete Column-to-Column Joint Using the Steel Plate Hoop and Bolts Connection - Dawei Yuan; Qi Shang; Chun Han; Jianpeng Sun; Qingning Li (Advances in Civil Engineering)
The traditional precast concrete column-to-column connections are widely used in the prefabricated concrete frame structures in China. However, many studies on the column-to-column joints have demonstrated their complex forms and poor construction efficiency. To overcome these shortcomings, a new type column–column connection with steel plate hoop and bolts was designed and proposed. In order to reveal the seismic performance of this new type connection, four precast concrete columns and two cast-in-situ columns were tested by cyclic lateral loading. They were compared and analyzed from the aspects of test phenomenon, failure mode, load–displacement relationship, strength, and stiffness degradation. The results showed that the prefabricated columns with this new type connection had the same seismic performance as the cast-in-place columns. Additionally, the strain curves of longitudinal reinforcement, stirrups, and steel plate hoops were presented, and the force transmission mode of this novel connection was analyzed. The results indicated that the innovative connection had reliable force transmission mode, which can provide reference for the application of prefabricated frame structure in the earthquake area.